Competition for budget-constrained buyers: Exploring all-pay auctions - Cemil Selcuk (Cardiff University, Cardiff Business School, 2024)
When faced with budget-constrained bidders, all-pay auctions revenue-dominate standard auctions (Örst and second-price), which, in a competitive market, gives an edge to the all-pay format. An equilibrium in which sellers compete with standard auctions fails to exist if the all-pay format is available. Assuming the budget is not severely limited, in the unique symmetric equilibrium sellers compete with all-pay auctions.
Keywords: D4; D81; D83; 330; All-pay Auctions; Budget Constraints; Directed Search; Competing Auctions